The Urgency of Campaign Fund Transparency for Better Elections - Marpaung*, Linda Wahyu; Indrayani, Leni (Universitas Syiah Kuala, 2024)
General Elections are a mechanism that allows the people to exercise their sovereignty directly, open to all, free from interference, carried out secretly, honestly and fairly within the Unitary State of the Republic of Indonesia, on the basis of Pancasila and the Constitution of the Republic of Indonesia of 1945. Campaign finance reporting is an important aspect in maintaining integrity and fairness in the general election process, especially in the election of President and Vice President . Law no. 7 of 2017 concerning General Elections regulates in detail the obligation to report campaign funds. However, there are still various challenges faced in implementing this law. This research is a normative study namely an approach that refers to analysis based on established principles, norms, or rules. This research is descriptive in nature, where the aim is to provide a complete picture of the state of elections that are democratic as well as honest and fair. Campaign finance reporting has variations in campaign finance reporting practices indicating that not all candidate pairs and their supporting political parties consistently comply with reporting obligations in accordance with applicable law. Financial reports are submitted, but the use of campaign funds is often not transparent. This results in uncertainty in how campaign funds are used and whether their use is in accordance with the provisions of Law no. 7 of 2017 concerning General Elections .